Kiss me - Mallery, Susan (Don Mills, Ontario : HQN Books, 2015)
A loner cowboy finds the one woman who can capture his heart.
Keywords: Cowboys -- Fiction; Man-woman relationships -- Fiction; California -- Fiction; Love stories